The influence of oxygen and methane on nitrogen fixation in subarctic Sphagnum mosses - Kox, Martine A. R.; Aalto, Sanni L.; Penttilä, Timo; Ettwig, Katharina F.; Jetten, Mike S. M.; van Kessel, Maartje A. H. J. (AMB Express)
2018